THE IMPLEMENTATION OF ENGLISH MEDIUM INSTRUCTION IN THE CONTEXT OF HIGHER EDUCATION SYSTEM IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2023)
English medium instruction (EMI) is being used by a large number of universities in countries where English is not the official language to conduct their postsecondary teaching and learning activities. Not only does EMI provide teachers and students with exposure to a worldwide academic environment, but it also poses certain practical problems for the possible learning results. This study has mainly examined published research regarding instructors' and students' opinions of EMI in various non-English speaking universities in Uzbekistan and non-English speaking countries in order to learn about the actual experiences of all involved and the challenges they encounter in various disciplines' courses. In order to assist in developing comprehensive policies for the language of instruction in the higher education sector and to reduce the difficulties associated with obtaining learning outcomes, this study will support the stakes of assessments as well as implementation stage.